2018
DOI: 10.21511/ppm.16(2).2018.39
|View full text |Cite
|
Sign up to set email alerts
|

International postgraduate students’ perceptions of service quality

Abstract: South African universities have embraced a drive to internationalize in view of globalization. One of the widely adopted measures towards internationalization has been the recruitment of international postgraduate scholars. The rationale is to draw diverse knowledge and expertise from the international students. However, the University of KwaZulu Natal’s Westville campus has not managed to attract a significant number of international scholars. The trend suggests that the university is unable to meet the expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(7 reference statements)
0
4
0
1
Order By: Relevance
“…In the postgraduate studies market, institutions can further get competitive advantage from employability of graduates (which is a reflection of the quality of the institutions' programmes), local and international recognition or rankings, consistency of service delivery through proper leveraging of integrated management systems such as ERP which can improve cost management, and resource efficiency of administrative procedures (Soliman & Karia, 2017). Other researchers further assert that effective relationship management for both recruiting and retaining students is another potential source of competitive advantage in the market for postgraduate studies (Chaguluka, Beharry-Ramraj, & Amolo, 2018). Although the findings in the preceding studies relate to postgraduate students, their contexts are different to Zambia.…”
Section: Sources Of Competitive Advantagementioning
confidence: 91%
“…In the postgraduate studies market, institutions can further get competitive advantage from employability of graduates (which is a reflection of the quality of the institutions' programmes), local and international recognition or rankings, consistency of service delivery through proper leveraging of integrated management systems such as ERP which can improve cost management, and resource efficiency of administrative procedures (Soliman & Karia, 2017). Other researchers further assert that effective relationship management for both recruiting and retaining students is another potential source of competitive advantage in the market for postgraduate studies (Chaguluka, Beharry-Ramraj, & Amolo, 2018). Although the findings in the preceding studies relate to postgraduate students, their contexts are different to Zambia.…”
Section: Sources Of Competitive Advantagementioning
confidence: 91%
“…Parasuraman, Zeithaml e Berry, (1985) descreveram as expectativas do cliente como padrões ou pontos de referência que os clientes associam a experiência de um serviço. As expectativas são amplamente afetadas pela comunicação boca a boca de clientes anteriores e as comunicações externas que os prestadores de serviços transmitem aos clientes-alvo sobre os benefícios do serviço (Chaguluka et al, 2018). As percepções, por outro lado, são descritas como o julgamento dos usuários do serviço quanto ao desempenho de um serviço experimentado (Makoe & Nsamba, 2019).…”
Section: Instrumento De Intervenção -Servqualunclassified
“…This impacts students personally and professionally and has a strong financial impact on higher education institutions and the overall revenue generated by the education sector (OECD, 2018). Additionally, students with negative experiences might share their experiences with their peers, influencing their decision to go to the same institution which impacts the reputation of that institution (Chaguluka et al, 2018). Thus, tertiary institutions should primarily consider the psychological well-being of students (Saucedo et al, 2020).…”
Section: Research Rationalementioning
confidence: 99%
“…However, there is very limited research on understanding the role of institutions impacting students' PBW. Chaguluka et al (2018) conducted a quantitative study in a South African university to measure the quality of services provided at the institution. They reported that overall, students were dissatisfied with the quality of services provided at their institution and there was a gap between their expectations and the reality of the services.…”
Section: Role Of Institution and Support Servicesmentioning
confidence: 99%
See 1 more Smart Citation